Contemporary Latin America - Munck, Ronaldo (New York Palgrave Macmillan, 2012)
"Fully updated for the third edition, Contemporary Latin America provides an accessible concise introduction to the region. Historical context, the countries and their peoples provides a backdrop to broad-ranging coverage of politics, economy, society and culture and the continent's prospects today. "--
Machine generated contents note: -- Introduction Settings HistoryPolitical Economy SocietyPoliticsSocial Movements GovernanceCultureInternational Context Futures.
Includes bibliographical references and index.
Keywords: HISTORY / Latin America / General; POLITICAL SCIENCE / History & Theory; POLITICAL SCIENCE / General; Latin America -- Economic conditions -- 1982-; Latin America -- Social conditions -- 1982-; Latin America -- Politics and government -- 1980-; Latin America -- Foreign relations -- 1980-